USING MAPLE SOFTWARE IN MATHEMATICAL MODELING - Sadullayeva, Sabina (Журнал иностранных языков и лингвистики, 2024)
This article talks about the capabilities of one of the mathematical programs, Maple, its place and role in the educational process. Maple application software makes it easy to solve complex mathematical problems. The use of the Maple program in the educational process ensures an increase in the fundamentals of mathematical and technical education. Improves students' skills of applying theoretical knowledge to practice. Mathematical modeling on a personal computer using Maple is designed to teach problem solving. Assignments and exercises given as mathematical examples, practical problems and practical tasks can be completed without difficulty. In general, it is possible to find a quick and high-quality positive solution to problems suitable for applied mathematics programs intended for students of engineering and construction engineering.